PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, IKLIM KERJA DAN KEMAMPUAN GURU TERHADAP KINERJA GURU DI SEKOLAH MENENGAH PERTAMA SEKECAMATAN DOLOK BATU NANGGAR KABUPATEN SIMALUNGUN - Damanik, Jamal; Isman, Muhammad; Siregar, Astri Novia (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This research aims to determine: (1) The significant influence of the principal's leadership on teacher performance at the Junior High School in Dolok Batu Nanggar District, Simalungun Regency, (2) The significant influence of work climate on the performance of teachers at the Junior High School in Dolok Batu Nanggar District, Simalungun Regency, ( 3) The significant influence of teacher ability on teacher performance at the Junior High School in Dolok Batu Nanggar District, Simalungun Regency, (4) The significant influence of the principal's leadership, work climate and teacher ability together on the performance of teachers at the Junior High School in Dolok Batu Nanggar District, Simalungun Regency. . The population in this study were all junior high school teachers in Dolok Batu Nanggar District with a total of 106 teachers and the sample used in this research was 52 teachers. This research uses data analysis, namely multiple regression with a significance level of 0.05, then processing the data obtained with the help of the SPSS (Statistical Product and Service Solution) data program version 22.0. The results of the research show that: (1) There is a positive and significant influence between the principal's leadership on teacher performance in Junior High Schools in Dolok Batu Nanggar District, Simalungun Regency as seen from the value of tcount > ttable or 8.743 > 2.010; (2) There is a positive and significant influence between work climate on teacher performance at the Junior High School in Dolok Batu Nanggar District, Simalungun Regency, seen from the value of tcount > ttable or 9.135 > 2.010; (3) There is a positive and significant influence between teacher ability on teacher performance at the Junior High School in Dolok Batu Nanggar District, Simalungun Regency, seen from the value of tcount > ttable or 9.617 > 2.010; (4) There is a simultaneous influence of the principal's leadership, work climate, and teacher ability on teacher performance in Junior High Schools in Dolok Batu Nanggar District, Simalungun Regency as seen from the value of tcount > ttable based on data analysis obtained Fcount 36,199 > 2,798 Ftable and coefficient of determination (R Square) of 0.693 which indicates that 69.3% of teacher performance can be obtained and explained by the principal leadership variables (X1), work climate (X2), and teacher ability (X3). Meanwhile, the remaining 30.7% can be explained by other factors not explained in this study.